High Seeding Rates and Low Soil Nitrogen Environments Optimize Weed Suppression and Profitability in Organic No-Till Planted Soybean - Menalled, Uriel D.; Pethybridge, Sarah J.; Pelzer, Chris J.; Smith, Richard G.; DiTommaso, Antonio; Ryan, Matthew R. (Frontiers in Agronomy, 2021)
No-till planting crops into rolled-crimped cover crops can improve soil health while reducing labor and fuel requirements compared with traditional tillage-based production. However, little information is available to help farmers optimize the management of organic no-till planted crops. Weed suppression, crop yield, and profitability were assessed across soybean [Glycine max (L.) Merr.] seeding rates and soil nitrogen environments in an experiment conducted at two sites in central New York. Soybeans were no-till planted into rolled-crimped cereal rye (Secale cereale L.) at 0, 185,000, 371,000, 556,000, and 741,000 seeds ha-1. Three rates (0, 63, or 125 kg ha-1) of sodium nitrate (15-0-2) were applied across seeding rates to create different soil nitrogen environments. When pooled over sites, the lowest weed biomass occurred at the highest soybean density in the lowest soil nitrogen environment. An interaction was observed between soybean seeding rate and nitrogen treatments on weed communities. Soybean yield increased asymptotically with crop density and was not affected by nitrogen or site treatments. When pooled over nitrogen treatments and sites, partial returns to the soybean seeding rates were maximized at $2,238 ha-1 with 527,800 seeds ha-1. Results suggest that crop density is an important lever for optimizing weed suppression and crop yield in organic no-till soybean, and that managing for low soil nitrogen conditions may further enhance weed suppression while maintaining high yields.